Screening Cataract and Other Visual Impairment by PELITA Cadre to Build Vision Center in Lima Puluh Kota Regency - Ariesti, Andrini; Hendriati, Hendriati; Hidayat, Muhammad; Irayanti, Irayanti; Ilahi, Fitratul; Yuswir, Astria Rima Rara; Lonanda, Gama Agusto; Primasakti, Pattih; Roza, Silvia; Syafendra, Atika; Afelita, Tia; Putra, Heru Ardila; Suhery, Suhery; Irza, Metika Rahmasari; Lucyana, Lucyana; Maralaut, Azhardin; Zulferza, Jaka (Warta Pengabdian Andalas, 2025)
Eye diseases, particularly cataracts, are the leading cause of blindness worldwide. This community service program by the Department of Ophthalmology, Faculty of Medicine, Andalas University, was conducted at the Pangkalan Public Health Center, Lima Puluh Kota Regency, by empowering PELITA (Posyandu) cadres in early detection of cataracts. Methods included counseling, training, and eye examination simulations for 40 cadres, followed by community screening using visual acuity and anterior segment examinations. Evaluation was carried out with pre- and post-tests, satisfaction surveys, and follow-up on patients referred for surgery. The average cadre score improved from 68 (pre-test) to 74.5 (post-test), indicating increased knowledge. A total of 71 patients were screened, including 40 cataract and 8 pterygium cases; 26 cataract and 4 pterygium patients subsequently underwent surgery. Cadres reported high satisfaction with the training and expressed readiness to continue participation. This program demonstrates that cadre training is effective in improving early detection of cataracts and other visual impairments, and provides a foundation for establishing a Vision Center in Lima Puluh Kota.